2000
DOI: 10.1001/jama.284.11.1399
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficiency of Prostate-Specific Antigen Screening Strategies for Prostate Cancer Detection

Abstract: Recognizing that the efficacy of PSA screening is unproved, the standard strategy of annual PSA screening beginning at age 50 years appears to be less effective and more resource intensive compared with a strategy that begins earlier but screens biennially instead of annually. JAMA. 2000;284:1399-1405.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
62
0
9

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(73 citation statements)
references
References 26 publications
2
62
0
9
Order By: Relevance
“…In our own screening collective around two-thirds of all men had thus a low risk and could be seen at longer intervals. The Ross and colleagues working group were able to show that by adopting such an approach not only could costs be cut but mortality could also be reduced compared with early detection as from 50 years (13). Reduced mortality is attributable, first, to the fact that on comparing younger men with those over 50 years, the younger men have a higher probability of having a curable form of prostate cancer (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…In our own screening collective around two-thirds of all men had thus a low risk and could be seen at longer intervals. The Ross and colleagues working group were able to show that by adopting such an approach not only could costs be cut but mortality could also be reduced compared with early detection as from 50 years (13). Reduced mortality is attributable, first, to the fact that on comparing younger men with those over 50 years, the younger men have a higher probability of having a curable form of prostate cancer (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Short intervals increase drawbacks, such as overdiagnosis and costs of screening without necessarily improving efficacy in terms of advanced cancers prevented, whereas too long an interval is likely to miss potentially lethal tumors at curable stages. Both observational and simulation studies have recently suggested the alternative of biannual instead of annual screening with a minimal risk of nonlocalized cancer (17,18). Nonrandomized studies and modeling are, however, prone to several biases.…”
Section: Discussionmentioning
confidence: 99%
“…Ross et al (2000) report on a simulation model to compare simple strategies (e.g. no screening, and screening intervals of 1, 2, and 5 yrs) based on performance measures including the number of PSA tests per 1000 men and prostate cancer deaths prevented.…”
Section: Introductionmentioning
confidence: 99%